Association between serum sodium and sporadic Parkinson’s disease - Zhou, Wen; Xia, Qingqing; Liu, Duan; Li, Jun-ying; Gong, Liang (Frontiers in Neuroscience, 2025)
BackgroundThe correlation between serum sodium and sporadic Parkinson’s disease remains unclear currently. This study aimed to assess the association between serum sodium and sporadic Parkinson’s disease.ObjectiveThe ultimate goal is to gain a deeper understanding of the implications of this relationship between serum sodium and sporadic Parkinson’s disease.MethodsWe conducted a retrospective cross-sectional study involving 1,189 participants in PPMI cohort. Age, sex, education years, race, body mass index, calcium, alanine aminotransferase, aspartate aminotransferase, white blood cell, lymphocytes, neutrophils, monocytes, red blood cell, hemoglobin, platelets, total protein, albumin, serum uric acid, serum sodium, serum potassium, urea nitrogen, creatinine, serum glucose were obtained from all participants. Logistic regression, and smooth curve fitting were utilized to substantiate the research objectives.ResultsThe overall sporadic Parkinson’s disease was 77.5% (921/1189); it was 71.9% (143/199), 75.4% (295/391), 76.7% (171/223), and 83% (312/376) for serum sodium quantile1 (Q1, 130–138.9 mmol/L), quantile 2 (Q2, 139–140.9 mmol/L), quantile 3 (Q3, 141–141.9 mmol/L), and quantile 4 (Q4, 142–155 mmol/L), respectively (p = 0.011). Multivariate odds ratio regression adjusted for risk factors demonstrates a 1-unit increment in the serum sodium raises the risk of sporadic Parkinson’s disease by 1.11 times, respectively. Smooth splines analysis suggested a linear association between levels of serum sodium and risk of sporadic Parkinson’s disease (P nonlinearity = 0.5). An interaction was observed between serum sodium and sex in their influence on sporadic Parkinson’s disease (p < 0.05). Further exploratory subgroup analysis within the age and BMI groups showed that there were no significant interactions between the subgroups (all p values for interaction were > 0.05). Additional sensitivity analyses supported the primary findings and indicated the conclusions are robust.ConclusionThis study highlights the influence of inappropriate serum sodium on the risk of incident sporadic Parkinson’s disease, independent of confounders. The link between serum sodium and sporadic Parkinson’s disease is linear.